2019
DOI: 10.3390/ma12060856
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical and Histological Analysis of Titanium (Machined and Treated Surface) Versus Zirconia Implant Materials: An In Vivo Animal Study

Abstract: Objectives: The aim of this study was to perform an in vivo histological comparative evaluation of bone formation around titanium (machined and treated surface) and zirconia implants. For the present study were used 50 commercially pure titanium implants grade IV, being that 25 implants with a machined surface (TiM group), 25 implants with a treated surface (TiT group) and, 25 implants were manufactured in pure zirconia (Zr group). The implants (n = 20 per group) were installed in the tibia of 10 rabbits. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 41 publications
(54 reference statements)
1
12
0
Order By: Relevance
“…Thus, the present study had the aim of evaluated both implant models (regular and new implant mcrogeometry) with the same surface treatment, to verify the importance of this factor (the macrogeometry) in the early time period of osseointegration. Primary stability is a prerequisite for achieving osseointegration of implants [1,12,13,21,25,26]. This results from the mechanical union between the bone and the implant that minimizes micromovements between the two structures and prevents the formation of fibrous tissue at its interface.…”
Section: Plos Onementioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the present study had the aim of evaluated both implant models (regular and new implant mcrogeometry) with the same surface treatment, to verify the importance of this factor (the macrogeometry) in the early time period of osseointegration. Primary stability is a prerequisite for achieving osseointegration of implants [1,12,13,21,25,26]. This results from the mechanical union between the bone and the implant that minimizes micromovements between the two structures and prevents the formation of fibrous tissue at its interface.…”
Section: Plos Onementioning
confidence: 99%
“…Another biomechanical assay to assess implant osseointegration is the removal torque value (RTv), which provides values on the joint force between bone and implant [1,12,13]. Although this type of test is little used for destroying the sample, it is impossible to perform histology of these pieces, these higher measured values are indicative of a good bone-implant interaction [1], and are also indicative of whether or not mineralization of the newly formed bone occurred on the implant surface. We compare the both groups proposed based on the two time points (3-and 4-weeks) after implantation, with a highly significant and it is thus concluded that there is an important effect between the groups (p < 0.05).…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Animal selection, surgical management and care: Nine white rabbits (New Zealand), weighing between 4 and 4.5 kg, were used for the in vivo analysis. The animals received the standard care and management applied in previous studies performed by our research group [1,2,3]. The international guidelines of animal studies were applied.…”
Section: Methodsmentioning
confidence: 99%
“…For implantology concepts, the process of osseointegration for titanium implants is defined by the union between the implanted material and the bone tissue. The adequate union between them depends on the physical and chemical characteristics presented by the material, the surgical technique used and the patient’s conditions (general and local) [1,2,3,4]. Regarding the composition of the material, titanium is now used due to its excellent biological and mechanical properties [5,6], even when special treatments are not made on its surface (implants with smooth surfaces).…”
Section: Introductionmentioning
confidence: 99%